Reverse hybrid total hip arthroplasty: a survival analysis of 1082 consecutive cases with minimum five-year follow-up. (August 2018) - Jain, S.; Magra, M.; Dube, B.; Veysi, V. T.; Whitwell, G. S.; Aderinto, J. B.; Emerton, M. E.; Stone, M. H.; Pandit, H. G.
Abstract : Aims: This study aimed to evaluate implant survival of reverse hybrid total hip arthroplasty (THA) at medium-term follow-up. Patients and Methods: A consecutive series of 1082 THAs in 982 patients with mean follow-up of 7.9 years (5 to 11.3) is presented. Mean age was 69.2 years (21 to 94). Of these, 194 (17.9%) were in patients under 60 years, 663 (61.3%) in female patients and 348 (32.2%) performed by a trainee. Head size was 28 mm in 953 hips (88.1%) or 32 mm in 129 hips (11.9%). Survival analysis was performed and subgroups compared using log rank tests. Results: Ten-year survival (122 hips at risk) was 97.2% (95% confidence interval (CI) 95.77 to 98.11) for all-cause revision. There was no difference in survival by age (p = 0.50), gender (p = 0.78), head size (p = 0.63) or surgeon grade (p = 0.36). No acetabular components underwent revision for aseptic loosening in the entire series. Four (0.4%) aseptic stem failures occurred early at a mean of 2.5 years (0.6 to 4.8) and were associated with age under 60 years (p = 0.015). There was no difference in survival by gender (p = 0.12), head size (p = 0.43) or surgeon grade (p = 0.77) for stem revision. Conclusion: This is the largest reported study into reverse hybrid THA and it confirms successful outcomes, irrespective of age, gender, head size and surgeon grade. Cite this article: Bone Joint J 2018;100-B:1010–17.